Enhancing Teachers’ Competence in Hajj–Umrah Ritual Training through Role-Play and Multimedia Learning Media at SMA Muhammadiyah Weleri - Mamdukh Budiman; Iqbal Hidayatsyah Noor; Danusiri Danusiri; Sriyono Sriyono (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2026)
The program sought to strengthen the pedagogical capacity of teachers at SMA Muhammadiyah 01 Weleri, Kendal (Central Java), through the application of role‑playing methods and the use of tangible instructional media. Implemented through a participatory training model, the activities encompassed conceptual reinforcement, guided demonstrations, structured simulations and role‑playing exercises, as well as reflective discussions. Learning supports such as a Kaaba miniature and sequenced manāsik simulation materials were employed to promote hands‑on learning and active participation. The outcomes of the program indicate enhanced teacher understanding of both procedural and conceptual aspects of the rituals, increased confidence in facilitating simulation‑based instruction, and improved ability to design interactive and engaging lesson plans. The novelty of this program lies in integrating role-play pedagogy with tangible ritual-learning media to strengthen practical, student-centred religious instruction. These findings suggest policy implications for schools and teacher development programs, including the adoption of experiential manasik modules and the provision of ritual-learning kits to improve the quality of Islamic religious education.